Quantification of residual cryoprotectants and cytotoxicity in thawed bovine ovarian tissues after slow freezing or vitrification. Issue 3 (20th December 2021) - Sugishita, Yodo; Meng, Lingbo; Suzuki-Takahashi, Yuki; Nishimura, Sandy; Furuyama, Sayako; Uekawa, Atsushi; Tozawa-Ono, Akiko; Migitaka-Igarashi, Junko; Koizumi, Tomoe; Seino, Hibiki; Natsuki, Yasunori; Kubota, Manabu; et al.
Abstract: STUDY QUESTION: How much residual cryoprotectant remains in thawed/warmed ovarian tissues after slow freezing or vitrification? SUMMARY ANSWER: After thawing/warming, at least 60 min of diffusion washing in media was necessary to significantly reduce the residual cryoprotectants in ovarian tissues frozen by slow freezing or vitrification. WHAT IS KNOWN ALREADY: Ovarian tissue cryopreservation (OTC) by slow freezing has been the conventional method; while the vitrification method has gained popularity for its practicality. The main concern about vitrification is how much potentially toxic residual cryoprotectant remains in the warmed tissues at the time of transplantation. STUDY DESIGN, SIZE, DURATION: This was an animal study using the ovarian tissues from 20 bovine ovaries. The duration of this study was from 2018 to 2020. PARTICIPANTS/MATERIALS, SETTING, METHODS: Ovarian cortex tissues were prepared from 20 bovine ovaries and assigned randomly to groups of fresh (non-frozen) control, slow freezing with 1.5 M dimethyl sulfoxide (DMSO), 1.5 M 1, 2-propanediol (PROH) and vitrification with 35% ethylene glycol (EG). The residual cryoprotectant concentrations in thawed/warmed tissues were measured by gas chromatography at the following time points: frozen (before thawing/warming), 0 min (immediately after thawing/warming), 30, 60 and 120 min after diffusion washing in media. Next, the ultrastructural changes of primordial follicles, granulosa cells, organelles and stromal cells in the ovarian tissues (1 mm × 1 mm × 1 mm) were examined in fresh (non-frozen) control, slow freezing with DMSO or PROH and vitrification with EG groups. Real-time quantitative PCR was carried out to examine the expressions of poly (ADP-ribose) polymerase-1 (PARP1), a DNA damage sensor and caspase-3 (CASP3), an apoptosis precursor, in thawed/warmed ovarian tissues that were washed for either 0 or 120 min and subsequently in tissues that were ex vivo cultured for 24 or 48 h. The same set of tissues were also used to analyze the protein expressions of gamma H2A histone family member X (γH2AX) for DNA double-strand breaks and activated caspase-3 (AC3) for apoptosis by immunohistochemistry. MAIN RESULTS AND THE ROLE OF CHANCE: The residual cryoprotectant concentrations decreased with the extension of diffusion washing time. After 60 min washing, the differences of residual cryoprotectant between DMSO, PROH and EG were negligible ( P > 0.05). This washing did not affect the tissue integrity or significantly elevate the percentage of AC3 and γH2AX positive cells, indicating that tissues are safe and of good quality for transplantation. LARGE SCALE DATA: N/A. LIMITATIONS, REASONS FOR CAUTION: Since the study was performed with ovarian tissues from bovines, generalizability to humans may be limited. Potential changes in ovarian tissue beyond 120 min were not investigated. WIDER IMPLICATIONS OF THE FINDINGS: This study addresses concerns about the cytotoxicity of EG in warmed ovarian tissues and could provide insights when devising a standard vitrification protocol for OTC. STUDY FUNDING/COMPETING INTEREST(S): The study was funded by a Grant-in-Aid for Scientific Research (B) from the Japan Society for the Promotion of Science to N.S.